Inequality of opportunity in Brazil - François Bourguignon; Francisco H. G. Ferreira; Marta Menéndez (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2005)
This paper proposes a method to decompose earnings inequality into a component due to unequal opportunities and a residual term. Drawing on the distinction between 'circumstance' and 'effort' variables in John Roemer's work on equality of opportunity, we associate inequality of opportunities with the inequality attributable to circumstances which lie beyond the control of the individual such as her family background, her race and the region where she was born. We interpret the decomposition as establishing a lower bound on the contribution of opportunities to earnings inequality. We further decompose the effect of opportunities into a direct effect on earnings and an indirect component which works through the 'effort' variables. The decomposition is applied to the distributions of male and female earnings in Brazil, in 1996. While the residual term is large, observed circumstances nevertheless account for around a quarter of the value of the Theil index. Parental education is by far the most important circumstance affecting earnings, dwarfing the effects of race and place of birth.
Keywords: D31; D63; J62; 330; Einkommensverteilung; Bildungschancen; Familie; Rasse; Sozialer Status; Männliche Arbeitskräfte; Brasilien